Design and development of obstacle detection and warning device for above abdomen level - Anuar , Mohamed Kassim; Jamri , Mohd Saifuzam; Mohd Aras, Mohd Shahrieel; Ab Rashid, Mohd Zamzuri; Mohd Rusdy , Yaacob (2012)
This paper discussed on design and development of obstacle detection and warning device which is used for above abdomen level of human in order to support and guide the visually impaired person. This electronic device is an innovation product to support and help those visually impaired person such to have their own confident to travel independently. In the developed obstacle detection and warning device, the distance measurement sensor is used to detect the obstacles and headphone is used as the warning device to give the obstacle information to the user. The distance measurement sensor's input is processed via main controller and gives the warning signal to the headphone. The power supply is came from battery and also acquire from alternative energy such as solar energy in order to charge the battery. The proposed warning system is to combine the vibration method with audio method. The vibration method is the best solution to warn the visually impaired person because it uses touch sense of human when the system is run. In this paper, the effectiveness of the system gives command the direction of obstacle existence is very important and have been confirmed through simulation and experiment.